2023
DOI: 10.5070/g6011239
|View full text |Cite
|
Sign up to set email alerts
|

Reproducible research practices and transparency across linguistics

Agata Bochynska,
Liam Keeble,
Caitlin Halfacre
et al.

Abstract: Scientific studies of language span across many disciplines and provide evidence for social,  cultural, cognitive, technological, and biomedical studies of human nature and behavior. As it becomes increasingly empirical and quantitative, linguistics has been facing challenges and limitations of the scientific practices that pose barriers to reproducibility and replicability. One of the  proposed solutions to the widely acknowledged reproducibility and replicability crisis has been the impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 101 publications
0
0
0
Order By: Relevance
“…Importantly, statements of conflict of interest are underused in linguistic research. Bochynska et al (2023) surveyed open and transparent practices in linguistics and found that only 10% of the articles sampled included statements of conflict of interest, and, among those 10%, none declared any conflicts (See also Cristea & Ioannidis, 2018;Hardwicke et al, 2022Hardwicke et al, , 2020. Positionality statements are likely even less common.…”
Section: Positionality Statementsmentioning
confidence: 99%
See 4 more Smart Citations
“…Importantly, statements of conflict of interest are underused in linguistic research. Bochynska et al (2023) surveyed open and transparent practices in linguistics and found that only 10% of the articles sampled included statements of conflict of interest, and, among those 10%, none declared any conflicts (See also Cristea & Ioannidis, 2018;Hardwicke et al, 2022Hardwicke et al, , 2020. Positionality statements are likely even less common.…”
Section: Positionality Statementsmentioning
confidence: 99%
“…When submitting a study for publication, the positionality statement can be included in additional materials if the word limit is a concern. For examples of positionality statements in linguistic research, the interested reader is directed to Bochynska et al (2023) and Weissler et al (2023).…”
Section: Positionality Statementsmentioning
confidence: 99%
See 3 more Smart Citations